Appraisal of Solar Radiation with Modelling Approach for Solar Farm Design - Sua, Lutfu S.; Balo, Figen (Springer International Publishing, 2021)
Sun irradiation is a significant consideration in solar power systems’ feasibility. Many models were suggested to estimate solar radiation concentrations because there is a lack of meteorological data available in the field. On the contrary, the efficiency of these models depends heavily on climate and ecological variables. This is one of the main reasons for increasing the amount of models available. This study aims to determine the most appropriate models for two specific cities chosen in a specific climatic region and to design a photovoltaic system for maximum effectiveness under particular weather conditions in Turkey; for these cities’ solar energy potentials, a comparative analysis in the third climatic region is also offered. It aims at extending the study to other towns in the country’s remaining climatic areas and generating a detailed model of solar radiation. © Springer Nature Switzerland AG 2021. All rights are reserved.
Keywords: Data analysis; Global solar radiation; Photovoltaic; Renewable energy; Solar energy; Solar farm